Faktor-Faktor Yang Mempengaruhi Kelelahan Otot Pada Karyawan Pengergajian Kayu Di CV Kahwa Jaya Saw Mill Kota Jambi Tahun 2020 - Aryani, Ulfah; Entianopa, Entianopa; Mirsiyanto, Eko (Pena Medika Jurnal Kesehatan, 2020)
In carrying out work, a wood craftsman must carry out physical activity. In lifting and carrying the load is more on the muscles, especially on the back, which can cause muscle fatigue. The research objective was to determine the factors that influence muscle fatigue in sawmill employees at CV Kahwa Jaya Sawmill Jambi City in 2020. The population in this study was 33 workers. Samples were taken by total sampling technique which was carried out by filling out a questionnaire and calculating the pulse. The results were analyzed Univariate and Bivariate with the chi square test. The results of statistical analysis using chi-square showed that there was a relationship between nutritional status (0.031), workload (0.000) and no relationship with physical work attitude (0.588) with muscle fatigue. It is recommended that workers to reduce muscle fatigue should eat a nutritionally balanced diet that produces 35,000 calories consumed at breakfast and lunch and drink enough water at least 8 glasses a day. Keywords: Muscle Fatigue, Physical Work Attitude, Nutritional Status and Workload